Association of AluYb8 insertion/deletion polymorphism in the MUTYH gene with mtDNA maintain in the type 2 diabetes mellitus patients. (5th July 2015) - Guo, Wenwen; Zheng, Bixia; Guo, Dong; Cai, Zhenming; Wang, Yaping
Highlights: mtDNA mutation rates are not affected by AluYb8MUTYH variant. Increased mtDNA content might be a compensatory mechanism to oxidative stress. AluYb8MUTYH variant is associated with aberrant mtDNA maintenance in T2DM patients. Abstract: A common AluYb8 -element insertion/deletion polymorphism of the MUTYH gene ( AluYb8MUTYH ) is a novel genetic risk factor for type 2 diabetes mellitus (T2DM). In the present study, mtDNA sequencing analysis indicated that the mtDNA sequence heteroplasmy was not associated with AluYb8MUTYH polymorphism. To better understand the genetic risk for T2DM, we investigated the association of this polymorphism with mtDNA content, mtDNA breakage and mtDNA transcription in the leukocytes of T2DM patients. The mtDNA content and unbroken mtDNA were significantly increased in the mutant patients than in the wild-type patients ( P < 0.05, respectively). However, no association between mtDNA transcription and AluYb8MUTYH variant was observed. The results suggested that the AluYb8MUTYH variant was associated with an altered mtDNA maintain in T2DM patients. The high level of mtDNA content observed in the mutant patients may have resulted from inefficient base excision repair of mitochondrial MUTYH and a compensatory mechanism that is triggered by elevated oxidative stress.